Treatment of osteoarthritis using Synvisc in New Zealand white rabbit - Abdul Hamid, Zahana; Zulkifly, Ahmad Hafiz; Amri, Nur Fathonah; Abd. Rahim, Nour El Huda; Hassan, Habibah; Ibrahim, Mohd Zulfadzli; Mohd Jan, Nurul Hafiza; Abu Hassan, Salmah Anim; Mohd Zohari, Sarah Haryati; Zainal Abdullah, Muhamad Ezham; Abdul Jalil, Rosnani; Che Seman, Che Zarida (2023)
INTRODUCTION: Osteoarthritis (OA) is a degenerative joint disease affecting millions worldwide. Synvisc® is wildly used as a treatment for OA. This study will investigate the histological changes of OA in rabbits treated with Synvisc®.